Unconventional role of lysosomes in phagocytosis. (November 2020) - Westman, Johannes; Freeman, Spencer A.; Grinstein, Sergio
Abstract: Lysosomes are generally thought to be required only for the late stages of phagosome maturation, providing the proton pumps (V-ATPases) and hydrolases needed to acidify and degrade the ingested prey. A recent paper by Davis et al. (EMBO J. [2020], doi:10.15252/embj.2019104058) reports the involvement of lysosomes at a much earlier stage, namely in scission of phagosomes from the plasma membrane. Here we analyze these findings, highlighting a number of unexpected observations and unresolved questions.